(untitled) (Revista de História Regional, 2021)
The purpose of this article is to reflect on the role played by Bishop Jaime Luiz Coelho, bishop (1957-1979) and Archbishop (1979-1997) of Maringá-PR, punctuating his performance in front of parishes during the period in which Paranavaí belonged to the Diocese of Maringá. And specifically, to point out the conduct of the bishop in relation to the friars of the Carmelite Province of Bamberg, precursor missionaries who integrated the broad process of development of the Catholic institution in Paraná. The text analyzes the construction of the Catholic institution in Paraná as part of a process of territorial, demographic and civilizing development of the state, based on the concept of faith and territoriality proposed by cultural geography. The creation of the Diocese of Paranavaí, dismembered from the Diocese of Maringá, under the bishopric of Don Jaime and the leadership of the Carmelite friar, leads to conclude that the history of the Catholic Church in the New North and North of Paraná and the historical-social development of the region are processes linked to the ecclesiastical presence, carrying a civilizing project.